2020
DOI: 10.3390/ani10091662
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Dog–Dog and Dog–Human Cases of Aggression in Northern Italy

Abstract: In this survey, a caseload of aggressive dogs (n = 170) was analysed to increase the available information about biting dog characteristics, contribute to risk evaluation and improve bite prevention tools. All dog data were collected from questionnaires completed by veterinary behaviourists in Northern Italy. All dogs were referred to them by public authorities to be evaluated and treated due to the incidence of one or more episodes of aggression. Between the two groups of human-directed and dog-directed aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…There are a multitude of complex underlying causes of agonistic behaviour, including territory guarding, competition for resources and genetics [ 18 ]. Additionally, a survey of dog owners demonstrated that dogs who were never exercised were more likely to exhibit intraspecific aggression [ 1 ]. The participation in the current exercise regimen may have alleviated boredom and restlessness, decreasing the agonistic behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a multitude of complex underlying causes of agonistic behaviour, including territory guarding, competition for resources and genetics [ 18 ]. Additionally, a survey of dog owners demonstrated that dogs who were never exercised were more likely to exhibit intraspecific aggression [ 1 ]. The participation in the current exercise regimen may have alleviated boredom and restlessness, decreasing the agonistic behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Sled dogs regularly perform repetitive bouts of endurance exercise when training for, and throughout, a racing season. Regular exercise may decrease boredom and provide physical and mental stimulation for dogs, potentially leading to beneficial behavioural changes such as a decrease in destructive or aggressive behaviours [ 1 ]. However, excessive repetitive bouts of strenuous aerobic exercise can have deleterious physiological impacts, such as increasing oxidative stress [ 2 , 3 ], muscle damage [ 4 ] and promoting gut dysbiosis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main physiological changes are increases in blood pressure, changes in cortisol levels, body temperature, increases in heart rate and blood glucose levels. In terms of behavioral changes, activation takes place at this time of the sympathetic adrenal medullary axis and the hypothalamic-pituitary-adrenal cortex axis [30,[45][46][47].…”
Section: Motivationmentioning
confidence: 99%
“…Therefore, the issues of risk assessment are important, primarily based on two main aspects: the first is the ability to predict dog bite risk factors in the general canine population, and the second is how to assess and predict future risk to society [51][52][53]. In a study by Notari et al [45], it was suggested that aggressive behavior mainly related to early experience, bad socialization process, origins (genetics factor), and welfare of dogs can have play an important role in both intraspecific and interspecific aggression [20,44,[54][55][56][57][58].…”
Section: Possessiveness-relatedmentioning
confidence: 99%
“…A link was proposed between stress and the beginning of anxiety [ 4 ], which is considered an important psychological disorder in dogs [ 5 ]. Anxiety is a condition induced when an environmental stimulus is improperly perceived as dangerous or threatening, and it becomes pathological when it is continued or occurs without environmental conditions justifying it [ 6 ].…”
Section: Introductionmentioning
confidence: 99%